KONSEP PENDIDIKAN TAHDZIBUN NAFS DALAM PRESPEKTIF KITAB JAWAHIRUL ADAB SEBAGAI SOLUSI UNTUK MENGATASI KEJENUHAN BELAJAR ONLINE DI ERA PANDEMI - Thoriq Al Anshori; Bahroin Budiya; Nofi Sri Utami (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
This research aims to dig deeper into ethical or moral knowledge in the book of Jawahirul Adab by Ulama nusantara Sheikh Ahmad Nawawi bin Sheikh Abdul Hamid al-Qosimy Al Bulumanisi from Bulumanis Pati, this type of research is literature research, data collection using interactive methods using primary and secondary reference sources before carrying out data presentation. The results of this study that the book of Jawahirul Adab provides the explanation needed by the current generation especially to overcome the saturation of learning in the pandemic era which is classified into 3 parts, namely adab interacting with Allah swt, adab interacting with fellow humans, and adab interacting with themselves both physically (physical senses) and spiritual (heart), in addition this book has a moral education concept that is very useful in order to direct and enlighten as well as control the morals of learners in the pandemic era in order to overcome the saturation that befalls themselves, because if there is with God, neighbor and self has been good then it will be very easy to foster earnestness and determination in carrying out all positive daily routines.